Nanomaterials multifunctional behavior for enlightened cancer therapeutics. (February 2021) - Raju, Ganji Seeta Rama; Dariya, Begum; Mungamuri, Sathish Kumar; Chalikonda, Gayathri; Kang, Sung-Min; Khan, Ishaq N.; Sushma, Pinninti Santosh; Nagaraju, Ganji Purnachandra; Pavitra, Eluri; Han, Young-Kyu
Highlights: Different types of nanoparticles and their properties are reviewed. Various nanoparticle drug delivery systems are discussed. Internal and external stimuli-responsive systems are explored. Nanoparticles and their applications in cancer therapy are described. Abstract: Cancer is an outrageous disease with uncontrolled differentiation, growth, and migration to the other parts of the body. It is the second-most common cause of death both in the U.S. and worldwide. Current conventional therapies, though much improved and with better prognosis, have several limitations. Chemotherapeutic agents, for instance, are cytotoxic to both tumor and healthy cells, and the non-specific distribution of drugs at tumor sites limits the dose administered. Nanotechnology, which evolved from the coalescence and union of varied scientific disciplines, is a novel science that has been the focus of much research. This technology is generating more effective cancer therapies to overcome biomedical and biophysical barriers against standard interventions in the body; its unique magnetic, electrical, and structural properties make it a promising tool. This article reviews endogenous- and exogenous-based stimulus-responsive drug delivery systems designed to overcome the limitations of conventional therapies. The article also summarizes the study of nanomaterials, including polymeric, gold, silver, magnetic, and quantum dot nanoparticles. Though an array of drug delivery systems has so far been proposed, there remain many challenges and concerns that should be addressed in order to fill the gaps in the field. Prominence is given to drug delivery systems that employ external- and internal-based stimuli and that are emerging as promising tools for cancer therapeutics in clinical settings.